Barnacle Epibiosis on Sea Turtles in Korea: A West Pacific Region With Low Occurrence and Intensity of Chelonibia testudinaria (Cirripedia: Chelonibiidae) - Kim, Hyun Kyong; Chan, Benny K. K.; Yi, Changho; Kim, Il-Hun; Choi, Yu Na (Frontiers in Ecology and Evolution, 2022)
Loggerhead and green turtles inhabit all oceans except the polar regions. External surfaces of sea turtles are often colonized by epibiotic chelonibiid barnacles. Barnacle taxonomy studies in Korea began in 1985, but until present, no turtle barnacles were recorded. This suggests that either the diversity and frequency of occurrence of turtle barnacles in Korean waters are low or the turtle barnacles have been understudied. This study complies with data collected over 6 years of sea turtle stranding events in Korea (2015–2020). We examined the diversity, frequency, and intensity of turtle barnacle occurrence. Of the 55 recorded strandings, loggerhead turtles were the most common (58%), followed by green turtles (33%). Only one species of barnacle, Chelonibia testudinaria, was found on both loggerhead and green turtles. The frequency of barnacle occurrence on loggerhead turtles was 28%, with an intensity of 2.4 ± 2.7 barnacles per turtle. Notably, 11% of green turtles had barnacles, with an average of one individual per turtle. The frequency and intensity of barnacle occurrence on green turtles analyzed in this study were five times lower than that on green turtle populations in Okinawan, Bornean, and Australian waters in the Indo-Pacific. Based on these new data and the available literature, we speculated that the barnacle larval pools in cold, high-latitude Korean waters are smaller than those occurring in other locations in the Indo-Pacific. The frequency and intensity of occurrence of barnacles on loggerhead turtles in Korea fall within the range recorded in other Indo-Pacific locations. The longer migratory routes of loggerhead turtles allow them to pass through different larval pools in the Indo-Pacific water, exposing them to higher barnacle abundances.